2020
DOI: 10.1159/000507246
|View full text |Cite
|
Sign up to set email alerts
|

Disease Severity Is Associated with Alexithymia in Patients with Atopic Dermatitis

Abstract: Background: Atopic dermatitis (AD) is a chronic inflammatory skin disorder that is associated with higher rates of psychological disorders, but limited evidence supported the association with alexithymia, a psychoaffective dysfunction. Objectives: This study was aimed to investigate the occurrence of alexithymia in AD patients, compared to healthy subjects. Methods: This cross-sectional study assessed AD severity by the Eczema Area and Severity Index (EASI) score, sleeplessness and itch by a numeric rating sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…When considering only established alexithymia (i.e., TAS-20 score ≥61), the prevalence of 22.4% seen among our SSc patients was quite similar to that of patients with psoriasis (24.8%) (Sampogna et al, 2017) and atopic dermatitis (27.7%) (Chiricozzi et al, 2020), while it was lower than the one reported for patients with hidradenitis suppurativa (37.2%) (Chiricozzi et al, 2018). In the general population of other European countries the prevalence of alexithymia is approximately 10% (Mattila et al, 2006;Franz et al, 2008).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…When considering only established alexithymia (i.e., TAS-20 score ≥61), the prevalence of 22.4% seen among our SSc patients was quite similar to that of patients with psoriasis (24.8%) (Sampogna et al, 2017) and atopic dermatitis (27.7%) (Chiricozzi et al, 2020), while it was lower than the one reported for patients with hidradenitis suppurativa (37.2%) (Chiricozzi et al, 2018). In the general population of other European countries the prevalence of alexithymia is approximately 10% (Mattila et al, 2006;Franz et al, 2008).…”
Section: Discussionsupporting
confidence: 66%
“…Cronbach’s alpha was calculated to evaluate the internal consistency of the instruments. As to sample size, we hypothesized a prevalence of alexithymia of 25%, on the basis of data from other chronic dermatological diseases, such as psoriasis (24.8%) ( Sampogna et al, 2017 ) and atopic dermatitis (27.7%) ( Chiricozzi et al, 2020 ). In a sample of 60 patients, the 90% confidence interval is within ±8.5% of the measured value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, alexithymia was also assessed in other chronic inflammatory dermatoses. In patients with psoriasis the prevalence of alexithymia was 24.8% ( 10 ), whereas a similar percentage was observed in patients with atopic dermatitis (27.7%) ( 11 ). The inclusion of emotionalizing and fantasizing in BVAQ is a distinguishing factor between BVAQ and the commonly used TAS-20 ( 12 ).…”
Section: Discussionmentioning
confidence: 77%
“…Studies revealed a greater prevalence of clinically significant alexithymia in patients with AD compared to controls, up to 66.7% [34, 51]. Further, data suggest disease severity may predict alexithymia severity: for every one-point increase in Eczema Area and Severity Index (EASI), patients had a 9% enhanced likelihood of having a higher TAS-20 total score and an 11% increase in likelihood of having a clinically significant TAS-20 total score [51]. In terms of alexithymia’s psychosocial implications in AD patients, a correlation between TAS-20 total score and greater family dysfunction was reported [34].…”
Section: Resultsmentioning
confidence: 99%